The effects of immigrant women’s anxiety levels on their sexual distress: A cross-sectional study - Zibulnesa Makhdom; Zehra Demet Ust Tasgin (BMC Public Health)
Abstract Background During the migration process, people do not merely change their geographical location, but also enter a phase of interaction and adaptation between different cultures. Migration often leads to a radical break from cultural values and brings about profound changes in individuals’ lives. The literature suggests that individuals who become separated from their culture may experience psychosomatic symptoms such as anxiety and depression, and that there is a relationship between cultural adaptation and sexual life. The present research was conducted to determine the effects of immigrant women’s anxiety levels on their sexual distress. Methods This descriptive and cross-sectional study was conducted with 300 immigrant women living in Istanbul between March 15, 2024, and August 31, 2024. The research data were collected using the Information Form, Beck Anxiety Inventory, and Female Sexual Distress Scale. Number, percentage, mean, standard deviation, minimum and maximum scores, ANOVA, independent samples t-test, Cronbach’s α, Pearson’s correlation tests, and linear regression analysis were used to analyze the data. Results Women’s mean age is 32.56 ± 8.98, 22.7% are high school graduates, 63% have social security, and 28.3% live in traditional families. The highest number of immigrants are from Syria, and the most obvious reason for migration is war. Of immigrants, 37.3% preferred Türkiye since it is safe, and 54% experience communication barriers and social problems the most since they are immigrants. Women scored an average of 32.68 ± 17.32 points on the Beck Anxiety Inventory, and 59% had severe anxiety. Furthermore, they scored an average of 25.66 ± 15.03 points on the Female Sexual Distress Scale, and 74% had sexual distress. Conclusion There is a statistically significant, positive, and high-level correlation between women’s anxiety levels and sexual distress levels. The level of anxiety explains 88% of the change in sexual distress.